Ocular Manifestations of Vitamin A Deficiency Among the Rural Pre-School Children of North India - Arlappa Nimmathota; Balakrishna Nagalla; Laxmaiah Avula; Brahmam GNV (Journal of Ophthalmic Science, 2015)
Purpose: Vitamin A deficiency (VAD) is still a major nutritional problem of public health importance among the rural pre-school children in India, even after the implementation national vitamin A prophylaxis programme for prevention of nutritional blindness and ICDS have been in operation for more than three decades. The purpose of this communication is to assess the prevalence of ocular manifestations of vitamin A deficiency among rural pre-school children of north India. Methods: A community based cross-section study; adopting multi-stage random sampling procedure was carried out by NNMB among rural pre-school children of four north Indian states viz. Maharashtra, Madhya Pradesh, Orissa and West Bengal. A total of 36,111 rural pre-school children of 1-5years (Boys: 18408; Girls: 17703) were covered for this study. Results: The prevalence of conjunctival xerosis (2.5%), the first ocular sign of VAD and Bitot’s spot (0.9%), an objective ocular sign of VAD was higher than the cut-off values suggestive of public health nutritional problem among the rural children. While, the prevalence of night blindness, the first symptom VAD was reported among 0.5% of rural children. Similarly, the proportion of rural pre-school children with sub-clinical VAD was 64%, suggestive of severe public health importance. Conclusion: The prevalence of ocular manifestation and sub-clinical vitamin A deficiency was high among the rural children of north India. Therefore, rural communities are encouraged to consume diets rich in vitamin A and administer massive dose vitamin A solution to the children of under five for the prevention and control of vitamin A deficiency and its adverse impact on child morbidity and mortality.
Keywords: Vitamin A deficiency